2022
DOI: 10.3390/agriculture12030376
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Release from Vermicompost under Anaerobic Conditions in Two Contrasting Soils of Bangladesh and Its Effect on Wetland Rice Crop

Abstract: Although its mechanism of action, particularly under wetland condition, is not clearly understood, vermicompost, a good source of humus and plant nutrients, has been used as organic manure in many parts of the world in order to increase crop production. Here, an anaerobic incubation study and a field study were conducted to observe the nutrient release pattern from vermicompost and its influence on performance and nutrient uptake in wetland rice. Two contrasting soils, viz. highly weathered terrace soil and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
1
10
0
2
Order By: Relevance
“…For example, in a study by [30] on barley, rates ranging from 0 to 250 t ha −1 were examined, with the highest yield and biomass observed at 250 t ha −1 . The study by [31] found that a combination of 10 t ha −1 VC with mineral fertilizer resulted in the best treatment for wetland rice, considering yield parameters, grain yield, nutrient uptake (except S uptake), and N use efficiency. However, ref.…”
Section: Vermicompost Rates Appliedmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a study by [30] on barley, rates ranging from 0 to 250 t ha −1 were examined, with the highest yield and biomass observed at 250 t ha −1 . The study by [31] found that a combination of 10 t ha −1 VC with mineral fertilizer resulted in the best treatment for wetland rice, considering yield parameters, grain yield, nutrient uptake (except S uptake), and N use efficiency. However, ref.…”
Section: Vermicompost Rates Appliedmentioning
confidence: 99%
“…It is characterized by high microbial activity and a nutrient-rich composition, including essential elements like N, P, K, Ca, Mg, Fe, Mn, Zn, and Cu (Table 2). These nutrients are readily available and easily absorbed by plants, thanks to the biological effects of the compost, such as increased enzyme activity, beneficial microbial populations, and plant-growth-promoting substances like hormones [31].…”
Section: Microbial and Chemical Composition Of Vermicompostmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest nodulation in beans obtained from integrating bean varieties, VC, and three times foliar bactericide sprays at the 7‐ and 14‐day intervals (Table 7) can be attributed to increased nutrient supplementation for plant growth and/or prevention of bacterial pathogens. Multiple studies have also associated improved nodulation in beans with the availability and supply of essential nutrients, like P, S, zinc, and iron, which are required for root development, nodule initiation and development, N‐fixation, and other important metabolic processes in plants (Argaw & Mnalku, 2017; Bezabeh et al., 2021; Hoque et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Kết quả này phù hợp với nghiên cứu của Chang et al (2008) là khi bón phân đậu tương không làm tăng hàm lượng carbon hữu cơ và lượng N tổng số trong đất so với bón 100% phân vô cơ, trong khi các loại phân hữu cơ khác (phân bò, phân chuồng ủ hoai mục, phân gà) cho các chỉ tiêu này cao hơn rõ rệt. Trong khi đó, phân trùn quế chứa lượng hữu cơ lớn, dinh dưỡng cân bằng, tăng khả năng giữ nước và dinh dưỡng của đất, đồng thời còn chứa các chất điều tiết sinh trưởng như auxins, cytokinins và gibberilin và axit humic (Azarmi et al, 2009;Hoque et al, 2022) Hiệu quả kinh tế từ việc trồng dưa chuột ở các biện pháp bón phân khác nhau được trình bày ở Bảng 6. Kết quả cho thấy chỉ bón phân trùn quế hoặc phân đậu tương ở năm đầu cho doanh thu và lợi nhuận thấp.…”
Section: Hình 1 ảNh Hưởng Của Tăng Lượng Phân Hữu Cơ Và Giảm Lượng Ph...unclassified